Diversification of Cultivars and Production of Male Inflorescence Flours for More Sustainable Banana Cultivation - dos Ouros, Lucas Felipe [UNESP]; Leonel, Magali [UNESP]; Leonel, Sarita [UNESP]; Molha, Nicholas Zanette [UNESP]; de Jesus, Paulo Ricardo Rodrigues [UNESP]; Cândido, Hebert Teixeira; Tecchio, Marco Antonio [UNESP]; Rechsteiner, Mayra Schmidt [UNESP]; dos Ouros, Caio César (MDPI, 2025)
Banana inflorescences are usually discarded, but there has been interest in managing this by-product to turn it into a product with added value. Herein, the inflorescences of seven cultivars were processed into flour and evaluated for their physicochemical characteristics. The weight of the inflorescences ranged from 681.3 to 1245.4 g, with bracts accounting for more than 40%. The Prata Anã cultivar had the largest inflorescence. The part of the inflorescence was the main factor differentiating the flours, with the effect of the cultivar dependent on the part processed. All flours had high levels of fiber (27.70–41.91 g/100 g) and carbohydrates (19.30–33.96 g/100 g). The palm flours were differentiated by their higher levels of protein (17.4–19.4 g/100 g), and the flower flours by their higher levels of lipids (5.89–7.97 g/100 g). The bract flours had a higher water holding capacity (5.62–6.78%) and browning index (40.7–42). The bract and flower flours were less dissimilar. Results revealed the high nutritional quality of the flours and the prospect of using them as a non-conventional food source. Understanding the differences between banana inflorescence flours expands their possible uses and promotes sustainable agricultural production in terms of efficient banana by-product management.